2019
DOI: 10.3390/app9214634
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Sensing Strategy Based on Energy Detector for Spectrum Sensing

Abstract: Sensing strategy directly influences the sensing accuracy of a spectrum sensing scheme. As a result, the optimization of a sensing strategy appears to be of great significance for accuracy improvement in spectrum sensing. Motivated by this, a novel sensing strategy is proposed in this paper, where an improved tradeoff among detection probability, false-alarm probability and available throughput is obtained based on the energy detector. We provide the optimal sensing performance and exhibit its superiority in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…It has been found that, increasing L does not significantly affect the execution time. The authors in [46] derive an optimal threshold ξ opt for the detection task. A version of the traditional ED with an SNR-adaptive thresholding for multiple-input multiple-output (MIMO) systems is derived in [47].…”
Section: ) Generalized Energy Detection For Computational Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that, increasing L does not significantly affect the execution time. The authors in [46] derive an optimal threshold ξ opt for the detection task. A version of the traditional ED with an SNR-adaptive thresholding for multiple-input multiple-output (MIMO) systems is derived in [47].…”
Section: ) Generalized Energy Detection For Computational Optimizationmentioning
confidence: 99%
“…Implementation in real-world prototypes requires fast processing which can in the ED's case be provided by decreasing the number of samples used for the TS computation. Reliable detection can be achieved for SNR as low as −15 dB [46] with N being over 60 times smaller than the necessary for CLT approximation [33]. Substantial relaxation of N is possible even for some complex fading channels (such as Rayleigh/ Nakagami-2/α-κ-µ/α-η-µ) in γ < 0 dB [39], [65].…”
Section: ) Lessons Learnedmentioning
confidence: 99%
“…Among the methods used for spectrum sensing, energy detection (ED) [4][5][6][7][8] is the most commonly used one, due to its simplicity as well as its almost universal applicability. Alternative spectrum sensing approaches use eigenvalue-based algorithms [9], covariance-based detection methods [10,11], cyclostationary feature detection [12,13], or compressive sensing [14,15].…”
Section: Introductionmentioning
confidence: 99%